The Analysis Of Assertives And Expressives On The Students’ Speaking Exam In English Department Student Of STKIP BUDI DAYA - BINJAI - Ayu - Indari (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2020)
This paper is purposed to analyze of the assertives and expressives sentences on the students’ speaking exam in English Department Student of STKIP Budi Daya – Binjai. The population and the sample of the research are the fourth semester students of English Department totally 23 students which consists of 316 sentence of utterances. The data are taken on 7 July 2020. The result of analyzing of the assertives are the first position on the components of assertive is affirming which is 79 points on percentage is 30,74%. The second position is answering which is 73 points on percentage is 28,40%. The third position is identifying which is 27 points on percentage is 10,51%. The result of analyzing of the expressives are the first position is greeting which is 36 points on the percentage is 61,02% . The second position is thanking which is 19 points on the percentage is 32,20% and the third position is accepting which is 4 points on the percentage is 6,78%. The using of assertives is more common than expressives because there are many components in the assertives.